Analisis Kekuatan Shooting Pemain Sepak Bola SSB Perisai Muda - Ilal Lahdi; Deka Ismi Mori Saputra; Titis Wulandari; Raja Bani Pilitan; Khairul Saleh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Shooting ability is one of the fundamental techniques that plays a crucial role in determining a player's success in scoring goals in football. The effectiveness of a shooting technique is influenced not only by technical mastery but also by leg muscle strength, movement coordination, body balance, and the proper execution of movements from the preparation phase, execution phase, to the follow-through phase. However, the shooting strength of players at Perisai Muda Football School (SSB Perisai Muda) has never been descriptively analyzed as an evaluation tool for the coaching process. Therefore, this study aimed to determine the level of shooting strength of SSB Perisai Muda players based on the preparation phase, execution phase, and follow-through phase. This study employed a quantitative descriptive research method using a survey approach through a shooting test. The population consisted of players from Perisai Muda Football School (SSB Perisai Muda). The sample comprised 25 players, selected using the total sampling technique. The research instrument was a shooting distance test, in which each player performed three shooting attempts representing the preparation phase, execution phase, and follow-through phase. The data were analyzed using descriptive statistics in the form of frequency distributions and percentages and were then classified into four categories: very good, good, fair, and poor. The results showed that in the preparation phase, shooting ability was predominantly in the Good category, with 13 players (52%), followed by the Fair category with 11 players (44%), the Very Good category with 1 player (4%), and no players in the Poor category (0%). In the execution phase, the Good category remained dominant with 13 players (52%), while the Very Good category increased to 3 players (12%), the Fair category decreased to 8 players (32%), and the Poor category consisted of 1 player (4%). In the follow-through phase, shooting ability was predominantly in the Fair category with 12 players (48%), followed by the Good category with 10 players (40%), the Poor category with 3 players (12%), and no players achieved the Very Good category (0%). It can therefore be concluded that the overall shooting strength of SSB Perisai Muda players falls within the Good category, although the players were not able to consistently maintain their shooting performance across all phases, particularly during the follow-through phase.